TEMPERATUR DAN HUJAN EKSTRIM DI BANDARA SAM RATULANGI MANADO TAHUN 1987 – 2017 - Tulandi, Djeli A; Tumangkeng, Jeane Verra; Bororing, Eva valencia (Universitas Negeri Manado, 2020)
This research was conducted because of changes in extremeÂ climate events due to increased concentrations of greenhouse gases. In this study a study was conducted on the temperature index and extreme rainfall periods 1987-2017 at Sam Ratulangi Airport in Manado. This study aims to analyze changes in temperature and extreme rainfall at the Sam Ratulangi Airport in Manado, determine the extreme climate index based on daily temperature and rainfall data, presented temperature and rainfall data which were processed using R-Climdex software. Â The results show that the slope of the air temperature index at the Manado meteorological station has decreased including the index TX10p and TN10p which indicates the frequency of both cold temperatures at night and cold temperatures during the day. At the meteorological station Manado slope air temperature index tends to increase which indicates that the minimum temperature is warmer. The overall rainfall index has increased while the PRCPTOT index has decreased which shows the amount of rainfall in one year period at Sam Ratulangi airport in Manado.